2022
DOI: 10.7759/cureus.24263
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Whole Blood Transfusions in Civilian Trauma: A Review of Literature in Military and Civilian Trauma

Abstract: Resuscitation techniques for the management of adult trauma patients have evolved over the 20th century. Whole blood transfusions were previously used as the standard of care, whereas blood component therapy is the current method employed across most trauma centers across the United States. Prior to the transition, no studies were conducted to show improved efficacy of hemostatic potential in trauma patients. Recent conflicts in Iraq and Afghanistan have challenged the dogma that whole blood transfusions are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Безпечність та ефективність переливання цільної донор с ької к р ові з а о с т анні дв а де с я т и лі т т я багаторазово доведено в умовах війни. Практика використання цільної крові у США при травмі й пораненнях поступово впроваджується в цивільну медицину [92][93][94]. Останніми роками з'являється дедалі більше публікацій, в яких трансфузію одногрупової цільної крові порівнюють з трансфузією її компонентів у найефективнішому співвідношенні 1:1:1 [95].…”
Section: п е р е л и в а н н я к р о в і б е з п р о б и н а індивіду...unclassified
“…Безпечність та ефективність переливання цільної донор с ької к р ові з а о с т анні дв а де с я т и лі т т я багаторазово доведено в умовах війни. Практика використання цільної крові у США при травмі й пораненнях поступово впроваджується в цивільну медицину [92][93][94]. Останніми роками з'являється дедалі більше публікацій, в яких трансфузію одногрупової цільної крові порівнюють з трансфузією її компонентів у найефективнішому співвідношенні 1:1:1 [95].…”
Section: п е р е л и в а н н я к р о в і б е з п р о б и н а індивіду...unclassified
“…[32] Whole blood is a desirable fluid for patients with traumatic hemorrhagic shock. [33][34][35] It has the advantage of providing red blood cells, plasma, and platelets together in a unit, which simplifies and speeds the process of resuscitation, particularly in austere environments. [36] Shea et al [37] have reported that the use of low-titer group O whole blood is independently associated with improved survival compared to component therapy in adults with severe traumatic hemorrhage.…”
Section: Research Hotspots and Emerging Topicsmentioning
confidence: 99%
“…The benefits of transfusing LTOWB include more effective platelet therapy, reduced preservative transfusion preventing the dilution of the products, higher concentration of specific clotting factors, as well as the recommended 1:1:1 ratio of red blood cells, plasma, and platelets for trauma resuscitation within a single product [6]. Further, these benefits are delivered in a single product and transfusion versus multiple products and transfusions, which decreases the patient's exposure to multiple blood donors and the risk of blood borne disease transmission [6].…”
Section: Introductionmentioning
confidence: 99%